Traditional Wisdom and Modern Methods in Qibla Direction: A Multicultural Study of Sunan Geseng Great Mosque, Indonesia - Muhajir, Muhajir; Khusurur, Misbah; Suleman, Frangky; Karimullah, Suud Sarim; Kuklienė, Lina; Siripipatthanakul, Supaprawat (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2024)
The accuracy of the Qibla direction holds paramount importance in Islamic worship practices, particularly in historical mosques where traditional methods intersect with modern calculations. This study examines the case of the Sunan Geseng Great Mosque in Indonesia, established circa 1400 AD, where traditional supernatural methods of Qibla determination converge with contemporary astronomical calculations. This research investigates the historical method of Qibla direction determination and analyzes community perspectives on potential recalibration, examining the balance between preserving historical authenticity and ensuring religious accuracy. This qualitative research employs historical analysis and astronomical approaches. Data collection involved in-depth interviews with six key informants including religious leaders, mosque administrators, and community members, supplemented by astronomical measurements and historical document analysis. Astronomical calculations revealed a 4° 54' 55.5